Exploring the ketogenic diet’s potential in reducing neuroinflammation and modulating immune responses - Monda, Antonietta; La Torre, Maria Ester; Messina, Antonietta; Di Maio, Girolamo; Monda, Vincenzo; Moscatelli, Fiorenzo; De Stefano, Marida; La Marra, Marco; Padova, Marilena Di; Dipace, Anna; Limone, Pierpaolo; Casillo, Maria; et al. (Frontiers in Immunology, 2024)
The ketogenic diet (KD) is marked by a substantial decrease in carbohydrate intake and an elevated consumption of fats and proteins, leading to a metabolic state referred to as "ketosis," where fats become the primary source of energy. Recent research has underscored the potential advantages of the KD in mitigating the risk of various illnesses, including type 2 diabetes, hyperlipidemia, heart disease, and cancer. The macronutrient distribution in the KD typically entails high lipid intake, moderate protein consumption, and low carbohydrate intake. Restricting carbohydrates to below 50 g/day induces a catabolic state, prompting metabolic alterations such as gluconeogenesis and ketogenesis. Ketogenesis diminishes fat and glucose accumulation as energy reserves, stimulating the production of fatty acids. Neurodegenerative diseases, encompassing Alzheimer's disease, Parkinson's disease are hallmarked by persistent neuroinflammation. Evolving evidence indicates that immune activation and neuroinflammation play a significant role in the pathogenesis of these diseases. The protective effects of the KD are linked to the generation of ketone bodies (KB), which play a pivotal role in this dietary ha formattato: Inglese (Regno Unito), Evidenziato Formattato: Allineato a sinistra protocol. Considering these findings, this narrative review seeks to delve into the potential effects of the KD in neuroinflammation by modulating the immune response. Grasping the immunomodulatory effects of the KD on the central nervous system could offer valuable insights into innovative therapeutic approaches for these incapacitating conditions.